A chiral phosphoric acid catalyst for asymmetric construction of 1, 3-dioxanes1. Issue 58 (25th July 2015) - Matsumoto, Akira; Asano, Keisuke; Matsubara, Seijiro
<x xml:space="preserve">Abstract</x> A chiral phosphoric acid catalyst enabled enantioselective 1, 3-dioxane construction, useful for polyketide motif synthesis, via a hemiacetalization/intramolecular oxy-Michael addition cascade.